Theory and Practice of Model Transformation : 10th International Conference, ICMT 2017, Held as Part of STAF 2017, Marburg, Germany, July 17-18, 2017, Proceedings /: 10th International Conference, ICMT 2017, Held as Part of STAF 2017, Marburg, Germany, July 17-18, 2017, Proceedings. (2017) - Unknown
No abstract available